2013
DOI: 10.1177/1934578x1300801011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ploidy Change on Secondary Metabolites and Photochemical Efficiency in Solanum Bulbocastanum

Abstract: Plants are well known for producing a wide diversity of natural compounds and several strategies have been proposed to enhance their production. Among them, somatic chromosome doubling may represent an effective and inexpensive method. The objective of the current study was to investigate the effect of polyploidization on the leaf metabolic profile and content of tetraploids produced from a wild diploid (2n=2x=24) potato species, Solanum bulbocastanum Dun. Photochemical efficiency of tetraploids was also analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Betacyanins, the major pigments in fruit of diploid Hylocereus monacanthus and synthetic allotriploid, decreased following genome doubling (Cohen et al, 2013). Similarly, tetraploid genotypes of Solanum bulbocastanum displayed either similar or lower amounts of phenylpropanoids, tryptophan, tyrosine and α-chaconine compared to diploids (Caruso et al, 2013). Furthermore, non-targeted and targeted metabolic profiling of mature leaves from three doubled diploids of citrus and their diploid controls showed that primary metabolism takes priority over specialized metabolism in doubled diploid plants, since the levels of primary metabolites tended to increase and the levels of secondary metabolites tended to decrease (Tan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Betacyanins, the major pigments in fruit of diploid Hylocereus monacanthus and synthetic allotriploid, decreased following genome doubling (Cohen et al, 2013). Similarly, tetraploid genotypes of Solanum bulbocastanum displayed either similar or lower amounts of phenylpropanoids, tryptophan, tyrosine and α-chaconine compared to diploids (Caruso et al, 2013). Furthermore, non-targeted and targeted metabolic profiling of mature leaves from three doubled diploids of citrus and their diploid controls showed that primary metabolism takes priority over specialized metabolism in doubled diploid plants, since the levels of primary metabolites tended to increase and the levels of secondary metabolites tended to decrease (Tan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, manipulation with ploidy, as a biotechnological tool, could be useful in improving pharmaceutical value of medicinal plants, since synthetic autopolyploids usually exhibit increases in bioactive metabolite concentration compared to their diploid progenitors (Javadian et al, 2017;Kong et al, 2017;Lavania et al, 2012;Sadat Noori et al, 2017;Tavan et al, 2015;Xu et al, 2014). However, several studies have shown that polyploidization did not affect the metabolite production (Hull-Sanders et al, 2009;Wohlmuth et al, 2005) or even that the effect of polyploidy on the production of specialized metabolites was negative (Caruso et al, 2013;Cohen et al, 2013;Mansouri and Bagheri, 2017;Tan et al, 2017). Furthermore, in comparison with diploids, polyploids generally produce larger cells which can result in an increased size of plant structures such as leaves, flowers and fruit, increased biomass and often show greater resistance to biotic and abiotic stress (Lavania et al, 2012;Yildiz, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither it is possible in most of the studies we refer to in the paper. The exceptions are the studies dealing with the content of secondary metabolites working with synthetically created polyploids (Kim et al, 2004;Caruso et al, 2011Caruso et al, , 2013Lavania et al, 2012;Cohen et al, 2013;Xu et al, 2014). The fact that all these studies are dealing with plant chemistry nicely illustrates the fact that chemical studies on synthetic polyploids are much easier than ecological studies.…”
Section: Consequences Of Polyploidization?mentioning
confidence: 99%
“…O efeito da poliploidia na fotossíntese ainda não está bem elucidado, pois apesar de todas as enzimas envolvidas no processo estarem presentes nos cloroplastos e as plantas poliploides terem um grande número de cloroplastos no mesófilo, Caruso et al (2013) relatam taxas fotossintéticas similares entre plantas diploides e tetraploides.…”
Section: Medidas De Pigmentos Foliaresunclassified